SARS-CoV-2 entry factors are highly expressed in nasal epithelial cells together with innate immune genes - Sungnak, Waradon; Huang, Ni; Becavin, Christophe; Berg, Marijn; Queen, Rachel; Litvinukova, Monika; Talavera-Lopez, Carlos; Maatz, Henrike; Reichart, Daniel; Sampaziotis, Fotios; Worlock, Kaylee B.; Yoshida, Masahiro; et al. (Nature Medicine, 2020)
We investigated SARS-CoV-2 potential tropism by surveying expression of viral entry-associated genes in single-cell RNA-sequencing data from multiple tissues from healthy human donors. We co-detected these transcripts in specific respiratory, corneal and intestinal epithelial cells, potentially explaining the high efficiency of SARS-CoV-2 transmission. These genes are co-expressed in nasal epithelial cells with genes involved in innate immunity, highlighting the cells’ potential role in initial viral infection, spread and clearance. The study offers a useful resource for further lines of inquiry with valuable clinical samples from COVID-19 patients and we provide our data in a comprehensive, open and user-friendly fashion at www.covid19cellatlas.org.
CRIS-Team Scopus Importer:2023-03-08